Dose-Dependent Incidence of Hepatic Tumors in Adult Mice following Perinatal Exposure to Bisphenol A - Weinhouse, Caren (NLM-Export, 2014)
Background: Bisphenol A (BPA) is a high production volume chemical with hormone-like properties that has been implicated as a potential carcinogen. Early-life exposure has been linked to increased risk for precancerous lesions in mammary and prostate glands and the uterus, but no prior study has shown a significant association between BPA exposure and cancer development. Objective: We explored the effects of BPA exposure during gestation and lactation on adult incidence of hepatic tumors in mice. Methods: Isogenic mice were perinatally exposed to BPA through maternal diets containing one of four environmentally relevant doses of BPA (0, 50 ng, 50 μg, or 50 mg per kilogram of diet), and we followed approximately one male and one female per litter until they were 10 months of age. Animals were tested for known risk factors for hepatocellular carcinoma, including bacterial and viral infections. Results: We found dose-dependent incidence of hepatic tumors in 10-month-old BPA-exposed mice. Of the offspring examined, 23% presented with hepatic tumors or preneoplastic lesions. We observed a statistically significant dose–response relationship, with an odds ratio for neoplastic and preneoplastic lesions of 7.23 (95% CI: 3.23, 16.17) for mice exposed to 50 mg BPA/kg diet compared with unexposed controls. Observed early disease onset, absence of bacterial or viral infection, and lack of characteristic sexual dimorphism in tumor incidence support a nonclassical etiology. Conclusions: To our knowledge, this is the first report of a statistically significant association between BPA exposure and frank tumors in any organ. Our results link early-life exposure to BPA with the development of hepatic tumors in rodents, and have potential implications for human health and disease. Citation: Weinhouse C, Anderson OS, Bergin IL, Vandenbergh DJ, Gyekis JP, Dingman MA, Yang J, Dolinoy DC. 2014. Dose-dependent incidence of hepatic tumors in adult mice following perinatal exposure to bisphenol A. Environ Health Perspect 122:485–491; http://dx.doi.org/10.1289/ehp.1307449